Applying for jobs and internships in museums : a practical guide - Schloetzer, Martha M. (London : Routledge, Taylor & Francis Group, 2021)
Applying for Jobs and Internships in Museums offers a straightforward approach to applying for positions within a museum. Martha M. Schloetzer provides practical advice about the application and interview process that will prepare emerging museum professionals as they approach the profession. From reviewing job and internship postings to developing a solid resume and writing distinctive cover letters, this guide provides practical, sound advice for museum job seekers. Schloetzer integrates the stories of successful and unsuccessful interns and job applicants throughout the book's narrative, and recognizing the additional challenges faced by non-US nationals, the book also offers information specifically for international students seeking work experience in US museums. The insider information included in Applying for Jobs and Internships in Museums makes it a key resource for both a US and international audience interested in gaining museum experience in the US. It will be of particular interest to college-level and graduate school students, as well as recent graduates. The guide can also serve as a reference in the classroom, helping professors and instructors prepare students for the job search ahead.
Preface: Why intern -- Introduction: How to use this book -- An internship is not a job -- Write a great resume -- Cover letter writing -- Preparing for an interview -- Internships for international students and recent graduates -- Future-proofing your career.
OCLC-licensed vendor bibliographic record.
Keywords: BUSINESS & ECONOMICS / Careers / Job Hunting; Museums -- Vocational guidance; Museums -- Employees; Internship programs